2005
DOI: 10.1161/01.cir.0000153800.09920.40
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Inhibition Ameliorates the Transition to Myocardial Failure and Decreases Oxidative Stress and Inflammation in Mice With Chronic Pressure Overload

Abstract: Background-Although aldosterone, acting via mineralocorticoid receptors, causes left ventricular (LV) hypertrophy in experimental models of high-aldosterone hypertension, little is known about the role of aldosterone or mineralocorticoid receptors in mediating adverse remodeling in response to chronic pressure overload. Methods and Results-We used the mineralocorticoid receptor-selective antagonist eplerenone (EPL) to test the role of mineralocorticoid receptors in mediating the transition from hypertrophy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(155 citation statements)
references
References 60 publications
10
141
1
3
Order By: Relevance
“…Our findings support the studies of others showing that MR mediates vascular inflammation. For example, the MR antagonists decrease oxidative stress and vascular inflammation in animal models (17)(18)(19)(20)(21)44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings support the studies of others showing that MR mediates vascular inflammation. For example, the MR antagonists decrease oxidative stress and vascular inflammation in animal models (17)(18)(19)(20)(21)44).…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone infusion induces leukocyte infiltration into arteries of rats and increases the expression of proinflammatory markers (15,16). Mineralocorticoid receptor (MR) antagonists decrease monocyte infiltration into the vascular wall in hypertensive rats, in rats treated with aldosterone, and in hypertensive mice (17)(18)(19)(20)(21). Clinical studies also show that aldosterone increases markers of vascular inflammation.…”
mentioning
confidence: 99%
“…Mechanical stress due to pressure overload activates the renin-angiotensin-aldosterone system (RAAS), triggering inflammatory signaling and leading to downstream stimulation of TGF-β cascades. Neurohumoral mediators, cytokines, and growth factors directly stimulate a fibrogenic program, triggering myofibroblast conversion and stimulating synthesis of large amounts of structural matrix proteins (103)(104)(105)(106). Stress-induced fibroblast activation in the pressure-overloaded myocardium may also be indirect, at least in part, requiring stimulation of fibrogenic cascades in cardiomyocytes and immune cells.…”
Section: Ecm In Cardiac Pressure and Volume Overloadmentioning
confidence: 99%
“…7,8 Recent large clinical trials, both the Randomized Aldactone Evaluation Study (RALES) and Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival (EPHESUS) studies, and other animal studies have demonstrated the beneficial effects of mineralocorticoid receptor (MR) antagonists on the prognosis and ventricular remodeling. [9][10][11][12] However, little is known about the effects of the MR antagonist on atrial remodeling in hypertension. MR stimulation is linked to interstitial fibrosis, inflammation, hypertrophy and superoxide production in the heart, [13][14][15] all of which are known to provide a pathogenic substrate for AF.…”
Section: Introductionmentioning
confidence: 99%